2018
DOI: 10.1103/physrevd.98.114514
|View full text |Cite
|
Sign up to set email alerts
|

SO(4) invariant Higgs-Yukawa model with reduced staggered fermions

Abstract: We explore the phase structure of a four dimensional SO(4) invariant lattice Higgs-Yukawa model comprising four reduced staggered fermions interacting with a real scalar field. The fermions belong to the fundamental representation of the symmetry group while the three scalar field components transform in the self-dual representation of SO(4). The model is a generalization of a four fermion system with the same symmetries that has received recent attention because of its unusual phase structure comprising massl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Indeed, in this form, one can see that the kinetic term of this model is precisely the same as that considered in previous work with SO(4) invariant staggered fermions [3].…”
Section: Staggered Fermion Modelsupporting
confidence: 64%
See 2 more Smart Citations
“…Indeed, in this form, one can see that the kinetic term of this model is precisely the same as that considered in previous work with SO(4) invariant staggered fermions [3].…”
Section: Staggered Fermion Modelsupporting
confidence: 64%
“…In [3], we showed that it is possible to achieve symmetric mass generation in this model for large values of the Yukawa coupling and vanishing gauge coupling. In this paper, we show that a four-fermion condensate can also be obtained by using strong gauge interactions and small Yukawa coupling.…”
Section: Staggered Fermion Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…They exhibit hyperscaling with universal critical exponents at the IRFP, and these critical exponents are relevant for mass generation in BSM models [7]. Although still in early stages, non-perturbative lattice investigations of other possible mechanisms for fermion mass generation [11][12][13][14][15][16][17] are also important and interesting to pursue.…”
Section: Composite Higgsmentioning
confidence: 99%
“…Results for this model appeared in Ref. [6]. 1 In addition to its manifest SO(4) symmetry, the action is also invariant under a shift symmetry…”
Section: Lattice Action and Symmetriesmentioning
confidence: 99%